The Influence of Entrepreneurial Self-Efficacy, Perceived Access to Finance, and Green Entrepreneurial Orientation on Entrepreneurial Decision-Making - Dika Setiagraha; Raras Yogasnumurti; Rizal Napitupulu (Penerbit Jurnal Indonesia, 2026)
This study aims to analyze the influence of Entrepreneurial Self-Efficacy, Green Entrepreneurial Orientation, and Perceived Access to Financing on Entrepreneurial Decisions using a quantitative approach through a survey method involving 108 respondents who have experience or plans to start a business. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that all constructs meet the criteria for validity and reliability. The coefficient of determination (R²) of 0.46 indicates that Entrepreneurial Self-Efficacy, Perceived Access to Financing, and Green Entrepreneurial Orientation simultaneously explain 46% of the variance in Entrepreneurial Decisions. Hypothesis testing shows that Entrepreneurial Self-Efficacy (X1) and Perceived Access to Financing (X2) have a positive and significant effect on Entrepreneurial Decisions (Y), while Green Entrepreneurial Orientation (X3) has a positive but insignificant effect. These findings suggest that confidence in personal capabilities and ease of access to financing are the main factors driving entrepreneurial decisions, whereas green entrepreneurial orientation has not yet become a dominant consideration at the early stage.